EMERGING PATHWAYS TO GREEN PURCHASE INTENTION: DECODING THE INFLUENCE OF ENVIRONMENTAL AWARENESS, GREEN PERCEIVED VALUE AND TECHNOLOGY ADOPTION MODEL ANTECEDENTS ON CONSUMERS' PURCHASE INTENTION - Sabu Khan (Agora International Journal of Economical Sciences (AIJES), 2024)
Understanding the buying behaviour of consumers for green products has become an emerging issue. The purpose of present study is to assess purchase intention of consumers with respect to green products (environment friendly) shopping in India. Further, this study examines the role of environmental awareness, green perceived value, perceived usefulness and attitude towards using in building consumer intentions to purchase green products. Further, the study extends the TAM (Technology Adoption Model) by Davis (1989) by incorporating external variables like environmental awareness and green perceived value.This study examines the information gathered from 260 clients via a Google form survey. Structural equation modeling (SEM), validity and reliability testing, and exploratory factor analysis were conducted using the gathered data. The result of the present study shows that environmental awareness and green perceived value exert positive and differential effects on attitude towards using green products. The study also found that attitude and perceived usefulness are equally important for the purchase intention of customers towards green products. Implications of the present work are useful for academicians, marketers, customers, and policy makers.
Keywords: 330